2017
DOI: 10.1055/s-0043-112749
|View full text |Cite
|
Sign up to set email alerts
|

Focal Breast Lesions in Clinical CT Examinations of the Chest: A Retrospective Analysis

Abstract: ABSTR AC TPurpose Based on radiological reports, the percentage of breast cancers visualized as incidental findings in routine CT examinations is estimated at ≤ 2 %. In view of the rising number of CT examinations and the high prevalence of breast cancer, it was the goal of the present study to verify the frequency and image morphology of false-negative senological CT findings. Materials and MethodsAll first contrast-enhanced CT examinations of the chest in adult female patients carried out in 2012 were retros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 19 publications
(13 reference statements)
0
3
0
Order By: Relevance
“…In our current literature review, only a few researchers identified the CT features of incidental breast lesions (7,8,11,14,15). Very limitted researchers investigate breast lesion's imaging features with CT and have attempted to compare other imaging modalities (3,16,17).…”
Section: Discussionmentioning
confidence: 99%
“…In our current literature review, only a few researchers identified the CT features of incidental breast lesions (7,8,11,14,15). Very limitted researchers investigate breast lesion's imaging features with CT and have attempted to compare other imaging modalities (3,16,17).…”
Section: Discussionmentioning
confidence: 99%
“…Breast cancer is now the most common cancer and the leading cause of cancer-related deaths among women [ 1 ]. Despite not being a conventional method for assessing breast lesions, the growing prevalence and utilization of computed tomography have revealed that incidental breast lesions are detected in a range of 0.3% to 7.63% of cases [ 2 4 ]. Furthermore, 31.0% to 70.0% of these incidental breast lesions have been found to be malignant upon pathological findings [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…It is generally believed that CT is not as good as X-ray mammography to show microcalcification nor as accurate as ultrasound to diagnose breast cystic lesions, although it can incidentally detect breast cancer [17]. It is generally not capable to differentiate benign and malignant breast lesions [18]. However, with the development of radiomics [19][20][21], which can provide a comprehensive quantification of the tumor phenotype by analyzing robustly [10][11][12] a large set of quantitative data with characterization algorithms [22], it has been become possible to use imaging features for treatment monitoring and outcome prediction in various cancers [23,24].…”
Section: Introductionmentioning
confidence: 99%